Հայաստանի կոմկուսի 1920—1930-ական թթ. փաստաթղթերը Հայաստանյայց Եկեղեցու վերաբերյալ - Հարությունյան, Ավագ Ա. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Протоколы руководящих органов Центрального комитета Коммунистической партии Армении (Президиума (Бюро) и Секретариата), содержащие довольно интересную информацию о политике Коммунистической партии в отношении Армянской Апостольской Церкви и религиозных вопросах, являются важным источником с точки зрения объективного представления проблемы. Документы, переведенные с русского языка, публикуются впервые. В советское время они были помечены как «Секретно», «Совершенно секретно», «Особо секретно». The minutes of the governing bodies of the Central Committee of the Communist Party of Armenia (Presidium (Bureau) and Secretariat), containing quite interesting information about the policy of the Communist Party towards the Armenian Apostolic Church and religious issues, are an important source from the point of view of an objective presentation of the problem. The documents are published for the first time in translation from Russian. In Soviet times, they were marked as “Secret”, “Confidential”, “Top secret”.
Keywords: Պատմություն